How much of an accent? toward a model of contrastive rhetoric for writing centre tutors - Siddiqui, Asif (My University, 2012)
Topics: 1. Background to Research; 2. Dependent Variable – Contrastive Rhetoric; 3. Intervening Variable – Role of the Tutor; 4. Intervening Variable – Client Agency; 5. Intervening Variable – Contextual Factors; 6. Dependent Variable – Second Language Output; 7. Conclusion – How much of an accent?
Presented on March 8, 2012 Graduate Student Research Symposium (Hosted by Department of Sociology): (Ped)Antics held at the University of Calgary in Calgary, Alberta.
Keywords: tutors; contrastive rhetoric